Melatonin Enhances Proliferation and Modulates Differentiation of Neural Stem Cells Via Autophagy in Hyperglycemia. (14th January 2019) - Li, Haoyuan; Zhang, Yanmin; Liu, Shangming; Li, Fengpeng; Wang, Benlin; Wang, Jianjie; Cao, Lanfang; Xia, Tongliang; Yao, Qingyu; Chen, Haijun; Zhang, Yulin; Zhu, Xiaodong; et al.
Abstract : Dysfunction of neural stem cells (NSCs) has been linked to fetal neuropathy, one of the most devastating complications of gestational diabetes. Several studies have demonstrated that melatonin (Mel) exerted neuroprotective actions in various stresses. However, the role of autophagy and the involvement of Mel in NSCs in hyperglycemia (HG) have not yet been fully established. Here, we found that HG increased autophagy and autophagic flux of NSCs as evidenced by increasing LC3B II/I ratio, Beclin-1 expression, and autophagosomes. Moreover, Mel enhanced NSCs proliferation and self-renewal in HG with decreasing autophagy and activated mTOR signaling. Consistently, inhibition of autophagy by 3-Methyladenine (3-Ma) could assist Mel effects above, and induction of autophagy by Rapamycin (Rapa) could diminish Mel effects. Remarkably, HG induced premature differentiation of NSCs into neurons (Map2 positive cells) and astrocytes (GFAP positive cells). Furthermore, Mel diminished HG-induced premature differentiation and assisted NSCs in HG differentiation as that in normal condition. Coincidentally, inhibiting of NSCs autophagy by 3-Ma assisted Mel to modulate differentiation. However, increasing NSCs autophagy by Rapa disturbed the Mel effects and retarded NSCs differentiation. These findings suggested that Mel supplementation could contribute to mimicking normal NSCs proliferation and differentiation in fetal central nervous system by inhibiting autophagy in the context of gestational diabetes. Stem Cells 2019;37:504–515 : Abstract : NSCs were impaired proliferation and induced premature differentiation in hyperglycemia via autophagy. Mel could reverse the damaged proliferation by inhibiting autophagy, and Mel contributed NSCs to mimicking normal differentiation in HG. Mel is a potential supplement to prevent the neuropathy in fetal CNS.